Urgensi Prinsip Kejujuran dan Tanggung Jawab Sosial dalam Islam pada Perilaku Produsen Skincare di Era Bisnis Digital - Alief Aqsha Ulhawa; Malahayatie Malahayatie; Taufiq Taufiq (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
In the era of digital business, skincare manufacturers face great opportunities to reach the global market through digital media such as e-commerce and social media. However, this development also presents serious challenges, especially in implementing the principles of honesty and social responsibility. Honesty is a major foundation in Islam that is key to building consumer trust, especially in the digital world where direct interaction is minimal. Non-disclosure of product information and misleading promotions can damage a producer's reputation and disrupt the business ecosystem. Islamic social responsibility has also become very relevant given the increasing consumer awareness of sustainability issues and business ethics. This literature study examines the importance of the principles of honesty and social responsibility in the behavior of skincare manufacturers, especially in Indonesia. Based on previous research, the application of honesty, such as transparency of product information and sharia-compliant production processes, can increase consumer loyalty. Meanwhile, social responsibility, such as environmental conservation and community empowerment activities, helps create added value while improving brand image. However, manufacturers face challenges in implementing these values, including unfair competition, lack of regulation, and poor consumer education. This study concludes that implementing honesty and social responsibility in the skincare business not only strengthens consumer trust but also contributes to economic and social sustainability according to Islamic values. By applying these principles, manufacturers can create a business ecosystem that is ethical, equitable and provides benefits to society at large.